A new design way for cylindrical blades with adjustable inlet blade angles. (June 2019) - Yan, Jing; Liu, Xiaobing; Peng, Li; Li, Jianan
A new approach for cylindrical blade design is presented in this article. Authors of this article analyzed the main reasons which are responsible for the low efficiency of untwisted blades and found out that the shock losses along the blade leading edge are much higher than those of twisted blades. Furthermore, based on the analysis, this article proposed a new design approach that is different from the traditional one. This new approach can reduce hydraulic losses at blade leading edge and improve performance and efficiency of cylindrical blades. In the traditional design process, to draw blade projection in plan view, an incidence at intersection of blade leading edge and inner streamline on the meridional section is selected for calculating blade inlet angle accurately. Because the incidence and the blade inlet angle at the intersection of blade leading edge and outer streamline are formed automatically, the blade inlet angles at this point are not suitable for oncoming flow direction, generating noticeable shock losses at this place. In the new design program, blade inlet angles at both intersection points formed by blade leading edge and the outer, inner streamlines are accurately calculated. This makes the shock losses generated by blade leading edge be minimized. Moreover, in conventional design, the projection of blade pressure side into plan view consists of only one plane curve. In the new design way, projection of blade surface in plan view is composed of two curves joined smoothly and continuously. Two impellers with fundamentally identical geometrical parameters were designed and manufactured, and the only difference is that their cylindrical blades were calculated and configured by applying a traditional design method or a the new approach. Test findings from an open loop indicate that in a wide load range from 0.8 to 1.2 times design flow rate, both head and efficiency of the new pump were raised. Over the operating range, efficiency of the new pump increased by 0.5% to 2.7%. Particularly, for higher flow rate, pump performance was improved significantly, and the increase of efficiency at pump design point arrived at 2.7%. The results suggest that the new approach presented in this article offers an effective and useful means to improve performance of low specific speed pumps.